Recent applications of dioxinone derivatives for macrocyclic natural product and terpenoid synthesis - Wei, Kai; Zheng, Xinhua; Zhang, Hongbin (Frontiers in Chemistry, 2022)
Dioxinone derivatives, a class of acetoacetate derivatives, have attracted widespread attention because of their multiple reactive sites, high reactivity, unique chemical properties, and potential synthetic applications. The dioxinone group is also stable under a wide range of reaction conditions, including strong acids, as well as a variety of transition-metal-catalysed processes, such as olefin metathesis and Pd-mediated cross-coupling. The inherent reactivity and diverse applications of dioxinones make them valuable reactive intermediates in organic synthesis. The conversion of dioxinones to acylketenes and their subsequent nucleophilic capture is also an excellent strategy for synthesising β-keto acid derivatives, which can be applied even in complex molecular synthesis. This review focuses on the recent advances in the application of dioxinones in synthetic method research and the total synthesis of natural products, highlighting the exceptional utility of these synthetic methodologies in the construction of macrocyclic cores and terpenoid skeletons. In particular, successful transformations of dioxinone fragments are discussed.